Islamic Epistemology of Kuntowijoyo in Sharia Economic Development - Arsyadani, Achmad Arfinanto; Rohmanu, Abid (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This paper examines the integration of Kuntowijoyo's Islamic epistemology in the development of sharia economics. Kuntowijoyo emphasizes the importance of integrating empirical knowledge and revelation, outlining an Islamic scientific paradigm based on Islam, Indonesian identity, and modernity. In the context of sharia economics, principles such as tauhid, sharia, and ethics are implemented to create justice and welfare. This research employs a qualitative approach with literature analysis to explore the concept of prophetic social sciences and its application to issues in sharia economics, including riba, gharar, and profit-sharing mechanisms like mudharabah and musyarakah. The findings indicate that Kuntowijoyo's epistemological integration can provide guidance for a more comprehensive and responsive development of sharia economics that addresses the needs of society